Spatio-temporal evolution and driving forces of urban gravity centers and ecological security risk gravity centers in China - Peng Chen; Jiaojiao Duan; Yihan Wang (Ecological Indicators)
The accelerated growth of urban areas has resulted in a significant increase in demand for construction land, which has led to various challenges, including the emergence of unsustainable land-use patterns and environmental degradation. To gain a deeper understanding of the influence of gravity center migration on urban safety, we select 30 Chinese cities for analysis and apply various methods, such as the center-of-gravity technique, the construction of an ecological security risk index, and a comprehensive center of gravity, to conduct a thorough study of urban gravity centers, ecological security risk gravity centers, and migration trajectories between the two. Additionally, we analyze the driving factors behind these phenomena, offering insights to inform the coordinated development of urban construction and the ecological environment. Our findings reveal: (1) The migration trajectories of the urban gravity centers and the ecological security risk gravity centers are not entirely identical. The ecological security risk gravity centers are situated closer to the geometric centers. (2) The migration trajectories can be broadly divided into two phases: from 2000 to 2010, the migration distance of the urban gravity centers in larger cities exceeded that in smaller cities, whereas from 2010 to 2020, the overall migration distance was more significant than that from 2000 to 2010. (3) The urban gravity centers and the ecological security risk gravity centers are influenced not only by natural factors such as elevation and terrain fluctuations but also by human factors based on population movement and development, as well as other factors, including infrastructure shifts driven by real-time policies.